Policy Review: Valuing Culture and Heritage Capital: A Framework Towards Informing Decision Making. (3rd April 2021) - Clark, Kate
ABSTRACT: The UK Department for Digital, Culture, Media and Sport have just published a new framework for developing ideas about culture and heritage capital. The aim is to provide research, data, guidance and tools to help organisations make a stronger case for investment in culture and heritage assets. The model will adapt an approach used for natural capital. This review article guardedly welcomes the initiative but notes that, as with natural capital, there are major conceptual challenges to be addressed. Leaving aside core theoretical issues, these include policy challenges such as defining cultural and heritage 'assets' and mapping their condition, the need to explore the whole idea of a 'services' model for cultural and heritage assets (which already exists for natural capital), questions around the validity of monetary values as proxies for heritage values, and major questions around the application of such models to different areas of heritage and cultural policy and practice. Cultural capital is not a new idea, but what is new is the attempt to take the monetisation of values a step further. This is an important debate, but it will require proper resources, and considerable engagement from the sectors, practitioners and communities in order to close the gap between economists and non-economists, and to genuinely help us all to better make the case for investing in culture and heritage.